Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.
\(\left(x+2\right)^3=\frac{1}{8}\)
\(\Rightarrow\left(x+2\right)^3=\left(\frac{1}{2}\right)^3\)
\(\Rightarrow x+2=\frac{1}{2}\)
\(\Rightarrow x=\frac{1}{2}-2\)
\(\Rightarrow x=-\frac{3}{2}\)
Vậy \(x=-\frac{3}{2}.\)
2.
b) Ta có:
\(5^5-5^4+5^3\)
\(=5^3.\left(5^2-5+1\right)\)
\(=5^3.\left(25-5+1\right)\)
\(=5^3.21\)
Vì \(21⋮7\) nên \(5^3.21⋮7.\)
\(\Rightarrow5^5-5^4+5^3⋮7\left(đpcm\right).\)
c) Ta có:
\(2^{19}+2^{21}+2^{22}\)
\(=2^{19}.\left(1+2^2+2^3\right)\)
\(=2^{19}.\left(1+4+8\right)\)
\(=2^{19}.13\)
Vì \(13⋮13\) nên \(2^{19}.13⋮13.\)
\(\Rightarrow2^{19}+2^{21}+2^{22}⋮13\left(đpcm\right).\)
Chúc bạn học tốt!
Đặt A=\(3^1+3^2+3^3+3^4+...+3^{99}+3^{100}\)
A=\(\left(3^1+3^2\right)+\left(3^3+3^4\right)+...+\left(3^{99}+3^{100}\right)\)
A=\(3^1\left(1+3\right)+3^3\left(1+3\right)+...+3^{99}\left(1+3\right)\)
A=\(3^1\cdot4+3^3\cdot4+...+3^{99}\cdot4\)
A=\(4\left(3^1+3^3+...+3^{99}\right)⋮4\left(đpcm\right)\)
1 + 2 + 22 + 23 + .... + 2100
= (1 + 2) + (22 + 23) + .... + (299 + 2100)
= 3 + 22.(1 + 2) + ..... + 299.(1 + 2)
= 3 + 22 . 3 + .... + 299 . 3
= 3.(1 + 22 + .... + 299)
1+2+22+23+...+2100
=(1+2)+(22+23)+...+(299+2100)
= 3 + 22x(1+2)+24x(1+2)+...+299x(1+2)
= 3 + 22 x3 + 24 x3+...+299 x3
Vậy 1+2+22+...+2100 chia hết cho 3